2022
DOI: 10.55133/eji.290205
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Histidine rich glycoprotein, a novel biomarker for sepsis, with traditional biomarkers in adult ICU patients

Abstract: Sepsis is a major public healthcare problem. It remains a significant cause of morbidity and mortality in intensive care units (ICU) all over the world. A lifesaving early specific diagnosis and treatment is a challenge as no gold standard technique exists that can alone allow a rapid and reliable diagnosis of sepsis. Histidine-rich glycoprotein (HRG) is a promising new biomarker of sepsis that can contribute to enhance current sepsis diagnostic tools. The current study aimed to evaluate HRG as a diagnostic bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several studies have pointed out that there is a close association between elevated levels of sMR and macrophage activation and enhanced phagocytic activity [40]. It has also been found that serum sCD163 level can be used for early diagnosis of sepsis and identification of severe sepsis, and its diagnostic value has obvious advantages compared with PCT and CRP [41]. In another study, the diagnostic value of sMR for sepsis was found to be significantly higher than that of sCD163 and CRP.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have pointed out that there is a close association between elevated levels of sMR and macrophage activation and enhanced phagocytic activity [40]. It has also been found that serum sCD163 level can be used for early diagnosis of sepsis and identification of severe sepsis, and its diagnostic value has obvious advantages compared with PCT and CRP [41]. In another study, the diagnostic value of sMR for sepsis was found to be significantly higher than that of sCD163 and CRP.…”
Section: Discussionmentioning
confidence: 98%